Menggagas Epistemologi Tafsir Alquran yang Holistik - Andi Rosa (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2017)
This paper aims to examine the epistemology of thematic Qur’anic interpretation. The main characteristic of thematic Qur’anic interpretation that can answer questions comprehensively is rare. The focus of this paper is how to implement the holistic epistemology of thematic Qur’anic interpretation to be a source of reference in Qur’anic interpretation. Analytical study of thematic analysis on Qur’anic thematic epistemology conducted by researchers of Qur’anic studies offered a new term that is a holistic epistemology of Qur’anic interpretation. The formulations of its epistemology explained in table 1.2 and table 1.3 in the paper. This paper shows the correlation of the thematic tafsir with many issues occurred in reality. This concept argued to be a solution in a dialogical relation between text and context and give the solution to the problem faced in Muslim society.